2022
DOI: 10.1097/bpo.0000000000002189
|View full text |Cite
|
Sign up to set email alerts
|

Rare Presentation of Pediatric Multiple Enchondromatosis Limited to Single Ray or Single Nerve Distribution in the Hand: A Multicenter Case Series

Abstract: Background: Multiple enchondromas in the pediatric hand is a relatively rare occurrence and the literature regarding its incidence and treatment is sparse. Within this rare subset of patients, we identified a unique cohort in which lesions are confined to multiple bones in a single ray or adjacent rays within a single nerve distribution. We review the clinical and pathologic characteristics and describe the indications for and outcomes of treatment in this unique subset of patients as well as offer conjectures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…It can arise in every bone, age, and gender. [5][6][7][8] Although half of the cases in long tubular bones are first discovered incidentally on radiological images in the third or fourth decade of life, phalangeal enchondromas are almost always discovered with a pathologic fracture. Recent studies show some evidence regarding etiology of the enchondromas, which is physis growth abnormality related to the PTHR1 and IDH1/2 gene mutation.…”
Section: Introductionmentioning
confidence: 99%
“…It can arise in every bone, age, and gender. [5][6][7][8] Although half of the cases in long tubular bones are first discovered incidentally on radiological images in the third or fourth decade of life, phalangeal enchondromas are almost always discovered with a pathologic fracture. Recent studies show some evidence regarding etiology of the enchondromas, which is physis growth abnormality related to the PTHR1 and IDH1/2 gene mutation.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of lesions in enchondromatosis is widely variable but commonly presents predominantly on one side of the body [ 1 ]. Of interest, one multicenter study reported an atypical subset of Ollier disease in which enchondroma distribution occurred along a single nerve or single ray [ 4 ]. The distribution of lesions may be useful in determining the prognosis.…”
Section: Introductionmentioning
confidence: 99%